2014
DOI: 10.1016/j.jcf.2013.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Exocrine cell-derived microparticles in response to lipopolysaccharide promote endocrine dysfunction in cystic fibrosis

Abstract: During recurrent infections associated with CF, exocrine MPs may contribute to endocrine cell dysfunction via NF-κB pathways. Membrane CFTR dysfunction is associated with decreased insulin secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 28 publications
(37 reference statements)
1
17
0
Order By: Relevance
“…In line with our report, an increase of 48 to 72 h after liver reperfusion of MPs from activated cells endothelial origin has been recently reported in an ischemia/reperfusion model probably reflecting the regeneration phase [33]. Furthermore, recent publications from our laboratory indicate that MPs contribute to the cross-talk between exocrine and endocrine pancreatic cells [34]. after hepatectomy Fig.…”
Section: Endocrine Researchsupporting
confidence: 91%
“…In line with our report, an increase of 48 to 72 h after liver reperfusion of MPs from activated cells endothelial origin has been recently reported in an ischemia/reperfusion model probably reflecting the regeneration phase [33]. Furthermore, recent publications from our laboratory indicate that MPs contribute to the cross-talk between exocrine and endocrine pancreatic cells [34]. after hepatectomy Fig.…”
Section: Endocrine Researchsupporting
confidence: 91%
“…Previous data have already shown the delivery of a pro‐inflammatory signal by MPs from patients with diabetes to endothelial cells . We have also reported that MPs, shed by pancreatic exocrine cells isolated from a patient with cystic fibrosis, are able to activate the NF‐κB pathway under pro‐apoptotic conditions . In the present model, because we could evidence MP recapture by by‐stander cells after 28‐h treatment (data not shown), we decided to focus on the variations of MP release that were already significantly elevated after 24 h, while recapture was still undetectable.…”
Section: Discussionmentioning
confidence: 80%
“…Stress was applied when cells had reach 70% of confluence as reported elsewhere . For each stress procedure, a specific pharmacological modulation was applied.…”
Section: Methodsmentioning
confidence: 99%
“…75 Tan, et al, hypothesized that the mechanism for this association between ergot-derivatives and myocardial malfunction was the stimulation of serotonergic (5-HT2B) receptors in the myocardium that caused the development of subendocardial plaques of myofibroblasts and enhanced extracellular matrix formation in the atria and ventricles. 76 Turning to cases of valvular heart disease, a study in Naples, Italy of 50 Parkinson's disease patients on cabergoline and 50 age and sex matched patients not under treatment with a lysergamide, found that there was an approximately three times higher relative risk to develop moderate tricuspid valve regurgitation in patients with prolactinomas receiving cabergoline therapy than in age and sex-matched healthy controls. 77 Another case report linked aortic valve regurgitation after 12 months of cabergoline therapy in a 57-year old dementia patient.…”
Section: Cardiac Abnormalities and Valvular Heart Diseasementioning
confidence: 99%
“…A small number of case reports were found that discuss seizure or stroke during intracarotid amobarbital dosing, 357,358 but analysis of these publications suggest that these events are procedure-related and not substance-related. 76 There were some papers on the negative neurobehavioral effects on children born to women who used or abused the drug during pregnancy, but these were not thought to be relevant to the demographics of the volunteers in the historical military-sponsored human trials.…”
Section: Propylene Glycolmentioning
confidence: 99%